A semi-theoretical model for energy efficiency assessment of air source heat pump systems. (15th January 2021) - Xu, Zhaowei; Li, Hao; Shao, Shuangquan; Xu, Wei; Wang, Zhichao; Wang, Yichao; Sun, Xiaoyu; Yang, Qiang; Xu, Ce; Zhao, Wenyuan
Abstract: Although significant progress has been made in relation to air source heat pump (ASHP) modeling, it is difficult to reflect the actual dynamic characteristics of the start-up process by a completely theoretical model, and a regression model cannot reflect the energy efficiency differences between systems intuitively. A semi-theoretical model for fixed speed ASHP which considers the modifications of no-load power consumption, cycling losses and defrost discount has been developed based on the statistical analysis of field monitoring data. Thermodynamic perfectibility was introduced to evaluate the steady-state performance at continuous operation. By taking the running and cycle time as input parameters, it is possible to relate the operation mode to system energy efficiency. In the verification of the seasonal coefficient of performance, the error is < 10%. The identification of the cycling losses from field monitoring data illustrated that the impact of cycling losses drops off with the increase of the running time and the percentage of running time in an ON-OFF cycle. In energy efficiency diagnosis applications, the quantified losses concluded that the least energy efficient project is caused by no-load consumption and cycling losses. The application of the simulation integrated with building heating system illustrates that the proposed model cooperated with iterative algorithm can realize minute-by-minute dynamic simulation. This paper provides a foundation for operation strategy research and energy efficiency analysis of the fixed speed ASHP system. Highlights: A semi-theoretical model for fixed speed air source heat pump system is proposed. The no-load power consumption, cycling losses, and defrost discount are identified. The cycling losses decrease with the increase of t on and t on / t cycle . The energy efficiency diagnosis is realized by relating t on and t cycle to the SCOP .